BIMBINGAN DAN KONSELING UNTUK ANAK UNDERACHIEVER - Rahmawati, Rafika (Paradigma, 2015)
Underachiever is a child with a performance that does not comply with the conditions they are supposed to have. Many things can cause a child to be an underachiever. One reason is the teachers’ teaching methods that can not be enjoyed by children as they should. Another cause is the student’s learning style that can not be accommodated in the classroom. The condition is often associated with gifted underachiever. Guidance and counseling to help children understand the conditions underachiever themselves. In-depth guidance and counseling can also help the child adjust to learning in the classroom. Parental involvement in the treatment of children with problems can underachiever positive effect on child development. Keywords: underachiever, guidance and counseling.